Physical properties of polyacrylamide gels probed by AFM and rheology. (13th February 2015) - Abidine, Yara; Laurent, Valérie M.; Michel, Richard; Duperray, Alain; Palade, Liviu Iulian; Verdier, Claude
Abstract: Polymer gels have been shown to behave as viscoelastic materials but only a small amount of data is usually provided in the glass transition. In this paper, the dynamic moduli and of polyacrylamide hydrogels are investigated using both an AFM in contact force modulation mode and a classical rheometer. The validity is shown by the matching of the two techniques. Measurements are carried out on gels of increasing polymer concentration in a wide frequency range. A model based on fractional derivatives is successfully used, covering the whole frequency range., the plateau modulus, as well as several other parameters are obtained at low frequencies. The model also predicts the slope a of both moduli in the glass transition, and a transition frequency is introduced to separate the gel-like behavior with the glassy state. Its variation with polymer content c gives a dependence, in good agreement with previous theories. Therefore, the AFM data provides new information on the physics of polymer gels.